Reduced seagrass resilience due to environmental and anthropogenic effects may lead to future die-off events in Florida Bay - de Fouw, Jimmy; Madden, Christopher J.; Furman, Bradley T.; Hall, Margaret O.; Verstijnen, Yvon; Holthuijsen, Sander; Frankovich, Thomas A.; Strazisar, Theresa; Blaha, Michelle; Van Der Heide, Tjisse (Frontiers in Marine Science, 2024)
Coastal systems often depend on foundation species such as seagrasses that are supported by self-facilitation. Seagrass meadows, however, are threatened worldwide due to climate change and local human impact, disrupting self-facilitation leading to system instability. Florida Bay is a large seagrass dominated coastal ecosystem that suffered from multiple seagrass mortality events over the last half century driven by hypoxia, high water temperatures, hypersalinity, and high biological oxygen demand. These conditions reduce the amount of photosynthetically-derived oxygen in the plant causing sulphide intrusion into meristematic tissues. Using a bay-wide sampling design and long-term monitoring trends of seagrass condition, we investigated the current state of the meadows, sediment characteristics (e.g., organic matter, sulphide, nutrients) and discuss how climate stressors interact with plant and sediment oxygen dynamics. Our survey revealed that at sites where seagrass had been previously denuded by die-off, the dominant seagrass Thalassia testudinum had not recovered, while the pioneering seagrass Halodule wrightii recolonized the impacted areas. Organic matter and sulphide levels were higher at the impacted sites, apparently a persistent characteristic of the formerly dense T. testudinum meadows in central and western Florida Bay. These sediment conditions promote sulphide intrusion of T. testudinum belowground tissue under anoxic conditions. Plant oxidation initially buffers sulphide intrusion, but disruption of this oxidation mechanism due to changing environmental conditions results in widespread mortality and seagrass community collapse. Climate change cannot be fully mitigated by local management, however, attempts can be made to control critical salinity and oxygen levels by increasing freshwater input, reducing hypersalinity and aiming to keep the internal seagrass oxidation feedback intact. Our study shows that the Florida Bay seagrass ecosystem is still recovering four years post die-off and continues to be susceptible to future climate change and system degradation.